Wine health properties - Grzegorz Borenski; Magdalena Wójcik; Julita Poleszak; Przemysław Szabat; Marta Szabat; Joanna Milanowska (Kazimierz Wielki University, 2019)
Introduction: Wine is worldwide known drink with a long history. It is popular in many cultures and diets. It is a component of Mediterranean diet, which is an example of healthy eating. Red wine seems to be an essential component of the diet, since moderate consumption of wine is associated with lower risk and mortality from cardiovascular disease. The aim of the study: The purpose of this systemic review was to collect and analyse available data about health properties of wine. Material and method: Standard criteria were used to review the literature data. The search of articles in the PubMed database was carried out using the following keywords: wine, alcohol, cardiovascular, polyphenols. Description of the state of knowledge: Pro-health properties of alcohol depends mainly on the content of polyphenols. The most biologically active polyphenol is resveratrol. Light drinking of wine has multiple beneficial effects. It decreases level of total plasma cholesterol, low-density lipoprotein and increases high-density lipoprotein, lowers blood fibrinogen, thromboxane A, platelet stickiness, reducing insulin resistance, inhibits inflammation, improves endothelial function, fibrinolysis and increases plasma concentration of atrial natriuretic peptide. In addition it may have neuroprotective effect and beneficial effect on gut microbiota. Summary: Moderate wine consumption can be beneficial for our health, may protect against cardiovascular disease, atherosclerosis, hypertension, certain types of cancer, type 2 diabetes, neurological disorders and metabolic syndrome. Nevertheless, any amount of alcohol consumed can lead to alcohol addiction and there is a very thin line between drinking small amounts and abuse. Furthermore, there are studies indicating that small amounts of alcohol can also have a negative impact on health. This subject still needs more studies and clinical trials.